AKTIVITAS TABIR SURYA SPRAY EKSTRAK DAUN CEMPEDAK (ARTOCARPUS CHAMPEDEN SPRENG) SECARA IN VITRO - Putri, Shafa Tasya Nabila; Suryaningsih, Betty Ekawati (Jurnal Kedokteran Mulawarman, 2025)
Background: Sun exposure cause several unwanted effects, including premature aging of the skin and pigmentation One of theadverse effects is skin cancer or melanoma. Currently, skin cancer ranks third with the most cancer cases after breast cancer. Oneway to prevent the adverse effects of ultraviolet (UV) exposure is to use sunscreen. Sunscreen is a cosmetic preparation that canprotect the skin from sun exposure, Sunscreen on the market uses more chemicals, so it often triggers irritation. Indonesia with itswealth of natural resources has many plants that can be used as sunscreen that is safer because the irritating effects caused will belighter. Research is needed on sunscreen from natural ingredients of cempedak leaves which contain flavonoids in the form ofquercetin and function to protect the skin from the adverse effects of ultraviolet (UV) exposureObjectives: To determine the potential of cempedak leaf extract as a sunscreen spray.Method: This study uses a quantitative method of quasi-experimental design with a control group. There were four variations of extract concentrations used, F I; 0,25%, F II; 0,5%, F III; 0,75%, dan F IV; 0,5%+Zn.. Then the absorbance value was checked to determine the Sun Protection Factor (SPF). With data analysis using Kruskal Wallis and Mann WhitneyResult: Based on the results of laboratory tests, there is an increase in Sun Protection Factor (SPF) with every increase in theextract given. The results of the Kruskal Wallis statistical test p=0.000 (p<0.05) showed that there was a significant result betweenthe absorbance value and the variation in the concentration of the extract with the highest SPF result obtained in formula 3 with aresult of 25.79.Conclusion: Cempedak leaf extract has the potential to be used as a sunscreen spray.Keywords: sunscreen, cempedak leaves, flavonoid, spray, ultraviolet